HUBUNGAN FREKUENSI PENYELAMAN, LAMA MENYELAM, PILEK, DAN MEROKOK, TERHADAP KEJADIAN BAROTRAUMA TELINGA TENGAH PENYELAM TRADISIONAL - Martinus, Ishak; Hadisaputro, Suharyo; Munasik, Munasik (Universitas Tribhuwana Tunggadewi, 2020)
Inability to equate middle ear space pressure with the surrounding environment can cause tissue damage or barotrauma. Factors influencing the incidence of middle ear barotrauma in traditional divers are colds, smoking, frequency of diving and length of diving. The purpose of explaining the factors related to the occurrence of barotrauma in the middle ear of traditional breath-resistant divers. The analytic observational research design with cross sectional approach is supported by in-depth interviews, by conducting interviews using questionnaires and otoscopy examinations of respondents to determine the events of middle ear barotrauma. The study population was traditional divers, totaling 78 respondents. The dependent variable is the occurrence of barotrauma in the middle ear of traditional divers, the independent variable with colds, smoking habits, frequency of diving and length of diving, data analysis using bivariate and multivariate. Results as many as 32 people (41.0%) of 78 respondents experienced middle ear barotrauma. Bivariate analysis showed a correlation between the frequency of diving with the events of the middle ear barotrauama p = 0.012. Logistic regression test showed the significance value of the frequency of diving ≥ 4 days / week (p = 0.0106; PR = 5.310; 95% CI = 1.619-17.413). Conclusion of factors related to the incidence of middle ear barotrauma in traditional divers is the frequency of diving hari 4 days / week, with a probability of 38.13%.